A Study of Consumer Ethnocentrism in Korea in Terms of Consumer Decision Making (Self-Concepts, Collectivism and Country-of-Origin) - Kim, Soyoung (2009)
Among the barriers which should be considered before beginning global marketing, this research examined the consumer ethnocentrism in Korea by studying relationships between three factors(self-concepts, collectivism and country-of-origin) with the degree of consumer ethnocentrism. By conducting focus group interview with 22 Korean participants in age 20-30, it was found that Korean consumer in age 20-30 do not show strong consumer ethnocentrism. The degree of consumer ethnocentrism appears differently according to the three factors. Firstly, when the product category is related to self-concepts with high-involvement, Korean consumers consider brand names as the most important factor and consequently tend to prefer foreign brands which are popular among the young generation. Secondly, there is high possibility for Korean consumers that they can still prefer foreign brands to be recognised by peers even though the qualities of them are not guaranteed. Therefore, collectivism does affect consumer ethnocentrism. Thirdly, when there is a lack of information about a certain product category, Korean consumers tend to depend on country-of-origin to evaluate products and make a purchase decision. However, in this case, only the brands from developed countries can be considered as alternatives while those from developing countries cannot be included in the evoked sets of Korean consumers even if the qualities are perceived the same as those from developed countries. Managerial implications and suggestions for future research were also discussed in the research.